2009
DOI: 10.1242/jcs.055160
|View full text |Cite
|
Sign up to set email alerts
|

Differences in endoplasmic-reticulum quality control determine the cellular response to disease-associated mutants of proteolipid protein

Abstract: Missense mutations in human PLP1, the gene encoding myelin proteolipid protein (PLP), cause dysmyelinating PelizaeusMerzbacher disease of varying severity. Although disease pathology has been linked to retention of misfolded PLP in the endoplasmic reticulum (ER) and induction of the unfolded protein response (UPR), the molecular mechanisms that govern phenotypic heterogeneity remain poorly understood. To address this issue, we examined the cellular response to missense mutants of PLP that are associated with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 61 publications
2
41
0
Order By: Relevance
“…Prior studies in animal and human models have implicated ER stress as a pathogenic result of particular PLP1 mutations, 41,[67][68][69][70][71] but the larger PMD community has struggled to leverage these findings to treat the general PMD population. We suspect that this is due to intrinsic differences in the types of mutations being targeted.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies in animal and human models have implicated ER stress as a pathogenic result of particular PLP1 mutations, 41,[67][68][69][70][71] but the larger PMD community has struggled to leverage these findings to treat the general PMD population. We suspect that this is due to intrinsic differences in the types of mutations being targeted.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of ER stress and the subsequent UPR has been implicated in pathogenesis of multiple human inherited diseases, including cystic fibrosis (45), retinitis pigmentosa (46), CMT (22), and PMD (8,11). Although there is wide phenotypic variation in each of these diseases, even among the mutations in same genes, little is known about the factors that determine the difference in ER stress and the severity of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Gow and Lazzarini (10) reported a cellular mechanism that the amount of mutant PLP1 gene product accumulated in the ER accounts for disease severity in PMD. Recent studies showed that differences in the UPR (9) and ER quality control (11) have the potential to modulate disease severity. These reports suggest that retention of PLP1 mutants determines the severity of ER stress and clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in a broad clinical spectrum, ranging from severe PMD to milder spastic paraplegia type 2. 8,12,13 Accumulation of unfolded/misfolded proteins such as PLP1 mutants in the ER activates the unfolded protein response (UPR) by the three ER stress sensors: (1) inositolrequiring kinase 1 (IRE1, also known as ER-to-nucleus signaling 1); (2) protein kinase-like ER kinase (PERK, also known as eukaryotic translation initiation factor 2 alpha kinase 3); and (3) activating transcription factor 6 (ATF6). These sensors maintain ER homeostasis via three mechanisms: (1) an increase in ER folding capacity by enhancing transcription/translation of ER chaperones; (2) retrotranslocation of unfolded/misfolded proteins from the ER to the cytosol, followed by ER-associated degradation (ERAD) that is dependent on the ubiquitin-proteasome system; and (3) inhibition of protein synthesis, which prevents ER entry of secretory and membrane proteins.…”
Section: Introductionmentioning
confidence: 99%